57. Orbicularis oculi muscle ultrasound in myasthenia gravis (MG): Preliminary data. Issue 12 (December 2017) - Sartucci, F.; Bocci, T.; Di Rollo, A.; De Luca, C.; Bartolotta, M.; Barloscio, D.; Parenti, L.; Santin, M.
Abstract : Myasthenia Gravis (MG) is an autoimmune neuromuscular disease characterized by abnormal weakness and fatigability of some or all skeletal muscles. Among them, external ocular muscles are often affected resulting in diplopia and ptosis. Our aim was to investigate the usefulness of Muscular Ultrasound (MUS) to detect possible morphological changes of the orbicularis oculi muscle (OOM) pathognomonic of the disease. We investigated 7 patients with MG (3 m and 4 f; mean age: 66.3 yrs SEM: 7.7); data were compared with those of a control group of 10 healthy volunteers, matched for age and sex with patients. All cases were diagnosed clinically, by electromyography (nerve repetitive stimulation test and single fiber electromyography) and blood specific antibody titer. In addition, we performed OOM ultrasound by a Telemed Echo-wave II or Esaote MyLab Gamma device. We considered muscle thickness, echogenicity and muscle fiber continuity. The average thickness of OOM was reduced in patients with MG (1.41 mm SEM: 0.09) compared with controls (2.03 mm SEM: 0.25; P = 0.009); fiber muscle discontinuity was evident in all the 7 pts; echogenicity was visually analogous to controls. MUS of OOM may provide useful information and could represent an additional simple easy tool to investigate and probable help diagnosis in MG patients. Studies involving larger patients populations are required to confirm their true value.